Impact of inverter-based resources on transmission line relaying -part II: power swing protection - Jalilian, Amin; Robinson, Duane A. (Frontiers in Electronics, 2023)
The power swing characteristic of transmission lines (TLs) can be affected by the large-scale integration of inverter-based resources (IBRs), resulting in the maloperation of the legacy power swing blocking (PSB) and out-of-step tripping (OST) functions. This paper presents a brief review of power swing phenomena and the impact on power swing protection functions. In this regard, the impact of IBR integration of type-III, and type-IV wind turbine generation (WTG) on legacy power swing protection functions has been scrutinized. To do so, the performance of impedance-based PSB and OST functions during the IBR integration has been investigated via comprehensive simulation studies. The results show that under a system contingency and high IBR penetration, depending on the IBR technology, the system experiences frequency oscillations and swinging impedance trajectories which are different from those from synchronous generators, such that the reliable operation of the legacy PSB and OST functions can be jeopardized. Moreover, during power swing phenomena, the simulation results have found that the security of distance protection cannot be guaranteed and the fault ride-through requirements cannot be maintained when a high share of IBRs have been integrated.